Enhancing Student' Writing Skills through Miming Games - Setiawan, Lucky; Puspita, Nurul; Reftyawati, Dian (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
Writing is an essential skill that requires students to articulate their thoughts and convey messages through written texts. This is considered an essential skill that students must develop for their academic achievement. Miming activities offer a varied strategy for learning that enhances students’ communication skills, encourages their creativity, and promote active participation. Student often struggle with writing because they are afraid of making mistake in grammar, vocabulary, and language use. The purpose of this research was to enhance students’ writing skills through the use of miming games, with a particular focus on procedural texts, which are intended to explain how to perform or create something through a series of steps. The design of this research was quasi experimental. The eighth grade of MTS Mathla’ul Anwar served as the study’s population. The research sample was chosen using a cluster random sampling technique. Data was collected by using a pre-test and post-test. The result showed that the Sig. (2 tailed) value was 0.001, which is lower than α=0.05. This indicate that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, it can be concluded that miming games involve students through movement and action, creating a fun learning environment that helps them understand sequence, structure and vocabulary.